1996
DOI: 10.1136/bmj.313.7053.341
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of HIV load in semen of HIV positive patients with newly acquired sexually transmitted diseases

Abstract: Higher maternal levels of free estradiol in first compared to second pregnancy: early gestational differences. JNad Cancer Inst 1986;76:1035-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Viral RNA is frequently detectable in semen during all stages of disease, and the absolute levels of cell-free virus can be as high as those observed in plasma [Gupta et al, 1997;Coombs et al, 1998;Dyer et al, 1998]. Concurrent genital tract infection is directly related to elevated viral RNA and proviral DNA titres [Mayer and Anderson, 1995;Atkins et al, 1996;Cohen et al, 1997;Fiscus et al, 1998]. This increase is presumably caused by leukocyte infiltration together with increased viral replication and viral receptor and coreceptor expression via elevated cytokine release ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral RNA is frequently detectable in semen during all stages of disease, and the absolute levels of cell-free virus can be as high as those observed in plasma [Gupta et al, 1997;Coombs et al, 1998;Dyer et al, 1998]. Concurrent genital tract infection is directly related to elevated viral RNA and proviral DNA titres [Mayer and Anderson, 1995;Atkins et al, 1996;Cohen et al, 1997;Fiscus et al, 1998]. This increase is presumably caused by leukocyte infiltration together with increased viral replication and viral receptor and coreceptor expression via elevated cytokine release ].…”
Section: Introductionmentioning
confidence: 99%
“…14 In one study, HIV concentrations in semen were 8 times greater in men with clinical urethritis and 10 times greater in men with gonorrhea relative to those without clinical urethritis. 15 In addition, successful treatments of STIs demonstrate subsequent reductions of HIV in semen, 16 and treatment of symptomatic STIs can reduce HIV transmission to uninfected sex partners. 17 Thus, co-occurring STIs appear important in promoting infectivity in HIV-infected men.…”
Section: Introduction Smentioning
confidence: 99%
“…13 Another study from the United Kingdom showed small but statistically significant decreases in semen HIV-1 proviral load following treatment of three cases of GU and one case of symptomatic NGU. 20 These changes in proviral load might be expected given the marked, cellular inflammatory response observed in GU and the association between detectability of cell associated virus and semen leucocyte count. 8 However, increases in both cell free and cell associated HIV-1 in semen are important as both may be transmissible.…”
Section: Discussionmentioning
confidence: 99%